PENGARUH FASILITAS TERHADAP KEPUASAN TAMU MENGINAP DI HANNAH HOTEL SYARIAH PAINAN - Wedi Andesta (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
This study aims to determine the effect of room facilities on guest satisfaction staying at Hannah Hotel Syariah Painan. This research is a quantitative descriptive study with a causal associative approach. The number of samples in this study were 82 samples. The sampling method is propotionate stratified random sampling. Data is collected by questionnaire using a Likert scale. The data analysis technique used in this study is descriptive analysis using simple linear regression analysis. The results of this study indicate that: (1) room facilities are in the good category 54.88%, (2) guest satisfaction is in the excellent category 40.24%, (3) there is a guest satisfaction value increased by 16.843 units, there is a positive influence and significant between room facilities to guest satisfaction staying at Hannah Hotel Syariah Painan. The R square value obtained is 0.174, this means that room facilities variables have an effect of 17.4%.